2017
DOI: 10.1007/s13205-017-0692-y
|View full text |Cite
|
Sign up to set email alerts
|

Solid state fermentation (SSF): diversity of applications to valorize waste and biomass

Abstract: Solid state fermentation is currently used in a range of applications including classical applications, such as enzyme or antibiotic production, recently developed products, such as bioactive compounds and organic acids, new trends regarding bioethanol and biodiesel as sources of alternative energy, and biosurfactant molecules with environmental purposes of valorising unexploited biomass. This work summarizes the diversity of applications of solid state fermentation to valorize biomass regarding alternative en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(70 citation statements)
references
References 88 publications
0
70
0
Order By: Relevance
“…Solid-state fermentation (SSF) is described as the biotransformation that takes place in a solid matrix in the absence or near absence of free water [6]. SSF has received extra attention over the last few years as researchers explored the production of added-value compounds such as enzymes, antibiotics, bioactive compounds, biological control molecules, etc., by using biomass or by-products from other processes [7,8]. Several studies have reported the optimization of cellulases and hemicellulases' production due to their role in biofuel production and associated costs [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Solid-state fermentation (SSF) is described as the biotransformation that takes place in a solid matrix in the absence or near absence of free water [6]. SSF has received extra attention over the last few years as researchers explored the production of added-value compounds such as enzymes, antibiotics, bioactive compounds, biological control molecules, etc., by using biomass or by-products from other processes [7,8]. Several studies have reported the optimization of cellulases and hemicellulases' production due to their role in biofuel production and associated costs [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the selected potential fungal strains reduced the lignin and holocellulose contents of the substrates with respect to increase in incubation time. Li et al (2008) have reported that an efficient ligninolytic fungus F. concolor was significantly degraded and removed 13.07% of lignin and 7.62% of holocellulose contents of wheat straw.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, valorization of agro-industrial residues may offer distinctive economic, environmental, and strategic advantages [28]. Although submerged fermentation (SmF) has widely been used for microbial enzyme production, the solid state fermentation (SSF) has gained substantive interest due to its advantages [20], such as simplicity of media, machinery, control system, downstream processing or process scale-up, lower capital/operational cost, and energy and space requirement, increased enzyme yield, among others [4,12,14,31]. Process optimization has always been instrumental for industrial production.…”
Section: Introductionmentioning
confidence: 99%